Morphological and ultrastructural studies of Nostoc foliaceum Mougeot ex Born. et Flah. (Cyanophyceae) growing on soil - Vigna, Maria Susana (2008)
Nostoc foliaceum Mougeot ex Born. et Flah. (Nostocales, Nostocaceae) is restricted to North America and Europe, and its description was limited to Mougeot’s original illustrations (1854). This report would extend the geographic distribution to South America and on the basis of material collected from the field and cultured (Buenos Aires Province, Argentina), provides taxonomical characters by which this species can be compared with Nostoc commune Vaucher ex Born. et Flah. In addition, we completed this contribution with an exhaustive morphological and ultrastructural study, particularly the development and ultrastructure of the akinetes.